2023
DOI: 10.1186/s12903-023-02930-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of autogenous tooth bone graft is an efficient method of alveolar ridge preservation – meta-analysis and systematic review

Abstract: Background Ridge resorption following tooth extraction may be reduced by alveolar ridge preservation (ARP). Previous randomized clinical trials and systematic reviews have suggested that autogenous tooth bone graft (ATB) can be an effective alternative material for ARP. However, the results are heterogeneous. Therefore, our research aimed to evaluate the efficacy of ATB in ARP. Methods A systematic search was conducted in Cochrane Library, Embase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…reported 43 . This result was similar to a systemic review that showed the mean newly formed bone proportion of the autogenous tooth bone graft was 40%, and the residual graft proportion was 12% 44 …”
Section: Discussionsupporting
confidence: 85%
“…reported 43 . This result was similar to a systemic review that showed the mean newly formed bone proportion of the autogenous tooth bone graft was 40%, and the residual graft proportion was 12% 44 …”
Section: Discussionsupporting
confidence: 85%
“…The limitations of this investigation and the grafting material itself should be acknowledged. “Demand exceeding supply” is the primary sore point in autogenous tooth bone grafting [ 9 – 11 , 13 , 19 21 ]. In this investigation, this issue was also encountered.…”
Section: Discussionmentioning
confidence: 99%
“…However, its “rob Peter to pay Paul” supplying patterns resulted in high bone resorption and complex donor site postoperative complications [ 8 ]. There is accumulating evidence for using autogenous teeth as a grafting material for alveolar bone restoration, socket preservation, and maxillary sinus lifting, and this method shows excellent osteoconductivity, osteoinductivity and osteogenicity [ 9 , 10 ]. There have been no studies that have described the repair of bone defects of dentigerous cysts arising from mandibular third molar grafts prepared with autogenous tooth graft material [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the systematic review findings, the ADB can be an alternative, cost-effective, and sustainable biomaterial for alveolar ridge preservation [21]. Different graft materials are currently available for alveolar ridge preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, establishing a standardized point for the CBCT linear measurements is mandatory for accurate assessments. This study is aimed at evaluating the role of autogenous dentine biomaterials in preserving the alveolar ridge after extraction of a single retained root in the maxillary nonmolar sites by clinical, tomographical, and histological examinations with a surgical stent as a reference point [ 21 ]. We hypothesized a difference between spontaneous healing and preserved extraction sockets, while the null hypothesis is that there is no significant difference between spontaneous healing and preserved extraction sockets with ADB in terms of dimensional changes and healing characteristics.…”
Section: Introductionmentioning
confidence: 99%